ES 2020
DOI: 10.32782/2224-6282/156-25
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Covid-19 Pandemic on the Hotel Industry

Abstract: Поширення інфекційного захворювання COVID-19 та карантинні умови суттєво вплинули і продовжують негативно впливати на туристичний та готельний бізнес, тому є необхідність дослідження впливу та наслідків спричинених світовою кризою на готельний бізнес, зокрема, створення умов для поступового виходу з рівня збитковості готельних підприємств та запобігання стагнації в галузі. Готельні заклади зіштовхнулися з новими проблемами: відсутність гостей, закриття, падіння доходів, безпека співробітників і гостей. Готельн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The study confirmed the effectiveness of using technological solutions to adapt to the pandemic (Slava & Chyniak, 2021;Dolbneva, 2020;Vahner & Demko, 2020;Korzh & Onyshchuk, 2020;Slozhynska & Kovtun, 2020;Stakanov, 2020;Banerjee & Bhattacharya, 2020;Susilawati et al, 2020;Seleiman et al, 2020). Of course, many hotel companies aim to use combined sets of organizational and technological solutions to increase customer flows and enterprise outcomes.…”
Section: Resultsmentioning
confidence: 57%
“…The study confirmed the effectiveness of using technological solutions to adapt to the pandemic (Slava & Chyniak, 2021;Dolbneva, 2020;Vahner & Demko, 2020;Korzh & Onyshchuk, 2020;Slozhynska & Kovtun, 2020;Stakanov, 2020;Banerjee & Bhattacharya, 2020;Susilawati et al, 2020;Seleiman et al, 2020). Of course, many hotel companies aim to use combined sets of organizational and technological solutions to increase customer flows and enterprise outcomes.…”
Section: Resultsmentioning
confidence: 57%
“…In particular, the studies highlight the impact of the pandemic on the functioning of the labor market of Ukraine (Lavrynenko, Pyata & Akhmetov, 2020); changes due to the pandemic in the solvency of the population of Ukraine (Khayetska, Dolovanyuk, 2020); problems of the hotel industry that arose during the spread of the global pandemic (Korzh, Onyshchuk, 2020), as well as the reaction and adaptation of the educational systems of various countries to the consequences of the blockade, and even the national security of Ukraine through the prism of new conditions caused by the spread of the SARS-CoV-2 virus (Horbulin, Danyk, 2020).…”
Section: Analysis Of Crisis Phenomena In Recent Studies and Publicationsmentioning
confidence: 99%
“…Cyfrova ekonomika: trendy, ryzyky ta sotsialni determinanty. (2020) URL: https://www.kmu.gov.ua/ua/npas/pro-shvalennya-koncepciyi-rozvitku-cifrovoyi-ekonomiki-tasuspilstva-ukrayini-na-20182020-roki-ta-zatverdzhennya-pla-nu-zahodiv-shodo-yiyi-realizaciyi.…”
unclassified
“…1. Index of food and dairy products prices (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020) [6] According to the Food and Agriculture Organization, milk prices have fluctuated somewhat over the past decade. 2015-2016 were exceptional as a result of the global crisis, after which demand began to recover.…”
mentioning
confidence: 99%
See 1 more Smart Citation